Low-coverage whole genome sequencing of diverse Dioscorea bulbifera accessions for plastome resource development, polymorphic nuclear SSR identification, and phylogenetic analyses - Lu, Ruisen; Hu, Ke; Sun, Xiaoqin; Chen, Min (Frontiers in Plant Science, 2024)
Dioscorea bulbifera (Dioscoreaceae), a versatile herbaceous climber native to Africa and Asia, holds significant nutritional and medicinal value. Despite extensive characterization and genetic variability analyses of African accessions, studies on the genetic variation of this species in China are limited. To address this gap, we conducted low-coverage whole genome sequencing on D. bulbifera accessions from diverse regions across mainland China and Taiwan island. Our initial investigation encompassed comprehensive comparative plastome analyses of these D. bulbifera accessions, and developing plastome resources (including plastome-derived repetitive sequences, SSRs, and divergent hotspots). We also explored polymorphic nuclear SSRs and elucidated the intraspecific phylogeny of these accessions. Comparative plastome analyses revealed that D. bulbifera plastomes exhibited a conserved quadripartite structure with minimal size variation mainly attributed to intergenic spacer regions, reinforcing prior observations of a high degree of conservation within a species. We identified 46 to 52 dispersed repeats and 151 to 163 plastome-derived SSRs, as well as highlighted eight key divergent hotspots in these D. bulbifera accessions. Furthermore, we developed 2731 high-quality candidate polymorphic nuclear SSRs for D. bulbifera. Intraspecific phylogenetic analysis revealed three distinct clades, where accessions from Southeast China formed a sister group to those from South China and Taiwan island, and collectively, these two clades formed a sister group to the remaining accessions, indicating potential regional genetic divergence. These findings not only contributed to the understanding of the genetic variation of D. bulbifera, but also offered valuable resources for future research, breeding efforts, and utilization of this economically important plant species.